Chemical and in vitro toxicologic characterization of wintertime and springtime urban air particles with an aerodynamic diameter below 10 µm in Helsinki - Salonen, Raimo O.; Hälinen, Arja I.; Pennanen, Arto S.; Hirvonen, Maija-Riitta; Sillanpää, Markus; Hillamo, Risto; Shi, Tingming; Borm, Paul; Sandell, Erik; Koskentalo, Tarja; Aarnio, Päivi (Scandinavian Journal of Work, Environment & Health, 2004)
' ' OBJECTIVES ': 'The chemical composition and toxicity of wintertime urban air particles with an aerodynamic diameter of <10 µm (PM10), derived mostly from long-range transport and local combustion sources, were compared with those of springtime PM10 derived mostly from the resuspension of road dust. ' ' METHODS ': 'Water-soluble ions and elements and polycyclic aromatic hydrocarbons (PAH) were analyzed from seasonally pooled PM10 samples collected at a busy traffic site in Helsinki in 1999. These PM10 samples were also tested for cytotoxicity [3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyl-tetrazolium bromide test] and the production of proinflammatory cytokines [tumor necrosis factor alpha (TNF-α) and interleukin 6 (IL-6)] and nitric oxide (NO) in the mouse macrophage cell line RAW 264.7. Their oxidative capacity and the associated DNA (deoxyribonucleic acid) damage were investigated by electron paramagnetic resonance and the formation of 8-hydroxy-2´-deoxyguanosine (8-OH-DG) in isolated calf thymus DNA, respectively. ' ' RESULTS ': 'The late wintertime and springtime PM10 had similar compositions of water-soluble ions and elements but the winter PM10 had a higher content of PAH. The spring PM10 was a much more potent inducer of TNF-α and IL-6 production than the winter PM10 was, but there were no consistent differences in cytotoxic potency. In contrast, the winter PM10 was a significantly more potent inducer of NO production and 8-OH-DG formation. The large cytokine responses to the spring PM10 were caused by its insoluble fraction and largely inhibited by the endotoxin antagonist, polymyxin B. The transition metal chelator, deferoxamine, did not modify the proinflammatory or cytotoxic responses to the PM10 samples. ' ' CONCLUSIONS ': 'The toxicity profile of urban air PM10 changed with season in a subarctic climate. Particulate-bound endotoxin from soil gram-negative bacteria is suggested as a highly proinflammatory constituent of springtime resuspended road dust.
Keywords: aerodynamic diameter; chemical composition; chemical toxicology; cytokines; Helsinki; high-volume particulate sampling; in vitro toxicology; inflammation; metals; mouse macrophage; nitric oxide; oxidative deoxyribonucleic acid damage; polycyclic aromatic hydrocarbon; resuspension; spring; urban air particle; winter